The Pan-Sirtuin Inhibitor MC2494 Regulates Mitochondrial Function in a Leukemia Cell Line - Carafa, Vincenzo; Russo, Rosita; Della Torre, Laura; Cuomo, Francesca; Dell'Aversana, Carmela; Sarno, Federica; Sgueglia, Giulia; Di Donato, Marzia; Rotili, Dante; Mai, Antonello; Nebbioso, Angela; Cobellis, Gilda; et al. (Frontiers in Oncology, 2020)
The involvement of sirtuins (SIRTs) in modulating metabolic and stress response pathways is attracting growing scientific interest. Some SIRT family members are located in mitochondria, dynamic organelles that perform several crucial functions essential for eukaryotic life. Mitochondrial dysfunction has emerged as having a key role in a number of human diseases, including cancer. Here, we investigated mitochondrial damage resulting from treatment with a recently characterized pan-SIRT inhibitor, MC2494. MC2494 was able to block mitochondrial biogenesis and function in terms of ATP synthesis and energy metabolism, suggesting that it might orchestrate cell response to metabolic stress and thereby interfere with cancer promotion and progression. Targeting mitochondrial function could thus be considered a potential anticancer strategy for use in clinical therapy.